Implementasi Sustainable Development Goals (SDGs): Optimalisasi Peran Mahasiswa KKN dalam Meningkatkan Kesehatan Masyarakat Melalui Kegiatan KKN di Desa Mekar Mulio: Pengabdian - Eisya Dalila; Putri Regina Indriani; Siti Hajar; Indira Ayu Lestari; Athiyah; Rizka Agustina Pasaribu; Dilahasana; Rahma Wulan Aprilia; Nur Azila Rahayu Putri; Aulia Nur Azmi; Ahmad Laut Hasibuan; Shinta Marito Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Kuliah Kerja Nyata (KKN) program in Desa Mekar Mulia demonstrates the strategic role of students in advancing Sustainable Development Goals (SDGs). Recognizing the persistent health challenges in rural Indonesia, such as limited healthcare access and low health literacy, students implemented a community-based approach focused on SDG 3, which aims to ensure healthy lives and well-being. Through a qualitative case study, this paper analyzes the effectiveness of student initiatives, including the hands-on education of making herbal balms for common ailments like bloating and joint pain, as a practical and economical solution for residents. Furthermore, students engaged in collaborative efforts with the community, such as gotong royong (mutual cooperation) for environmental sanitation and providing education on waste management and the cultivation of medicinal plants and vegetables. This holistic approach not only improved public health awareness and practices but also strengthened the bond between students and the community, highlighting KKN as a viable model for sustainable, locally-relevant development.